MENINGKATKAN KEMAMPUAN MENULIS KALIMAT BERPOLA SPO MELALUI MEDIA SMS HANDPHONE BAGI ANAK TUNARUNGU KELAS V - Eslina - (Jurnal Penelitian Pendidikan Khusus, 2012)
This research starts with a case found two deaf students in fifth grade, where they are not capable of writing the SPO sentence, which is less precise in positioning the subject, predicate, and object, so that it’s hard to get the real meaning of that sentences. During this time, the teacher always use the tools like pen, book, and blackboard, word card, word sentence, and the students can not also stringing up words become sentences. This research is purposed to increase the deaf student ability to write the sentence with SPO pattern (LW and WP) in DV class SLB Amal Bhakti Sicincin.Deaf people is a person that pursued in communicating because they are having disparity of hearing function, less vocabulary, so that it’s hard for them in submitting and receiving information and as well as writing sentences. To overcome that matters, the proper solutions must be found, that is by using SMS through handphone, this media is the proper way in the study of writing sentences with SPO pattern. This research methods consist of kind of research, kind of this research is class action research, subject of research, subject of this research are two deaf students initial LW and WP, variable of this research  are independent and dependent variables, path of research using qualitative action that described through words in SMS Handphone, and quantitative action through SPO words that written by students.